2014
DOI: 10.1007/s13277-014-2754-7
|View full text |Cite
|
Sign up to set email alerts
|

Berberine-induced apoptosis in human breast cancer cells is mediated by reactive oxygen species generation and mitochondrial-related apoptotic pathway

Abstract: Berberine has drawn extensive attention toward their wide range of biochemical and pharmacological effects, including antineoplastic effect in recent years, but the precise mechanisms remain unclear. Treatment of human breast cancer cells (MCF-7 and MDA-MB-231 cells) with berberine induced inhibition of cell viability in concentration- and time-dependent manner irrespective of their estrogen receptor (ER) expression. Hoechst33342 staining confirmed berberine induced breast cancer cell apoptosis in time-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…In another research by Eom, Kim, So, Park, and Kim () demonstrated that BBR induces apoptosis by mediating endoplasmic reticulum stress and mitochondrial dysfunction in human glioblastoma T98G cells. This contrary side of BBR is applied in its therapeutic effect in cancer by promoting ROS generation and mitochondrial‐related apoptotic pathway (Xie et al, ). As a consequence, these evidences may prove that BBR has dual effect in the treatment of nervous diseases and its dose‐dependent manner may be one of the reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In another research by Eom, Kim, So, Park, and Kim () demonstrated that BBR induces apoptosis by mediating endoplasmic reticulum stress and mitochondrial dysfunction in human glioblastoma T98G cells. This contrary side of BBR is applied in its therapeutic effect in cancer by promoting ROS generation and mitochondrial‐related apoptotic pathway (Xie et al, ). As a consequence, these evidences may prove that BBR has dual effect in the treatment of nervous diseases and its dose‐dependent manner may be one of the reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been identified for the anti-proliferative effects of berberine, including down-regulation of cyclins A, D, cyclin-dependent kinase (CDK) 1, CDK4, MMP-2 and janus kinase 2 (Jak2)/vascular endothelial growth factor (VEGF)/NF-κB/activator protein 1 (AP-1) pathway, and induction of autophagic cell death via mTOR signaling pathway [149,155,156]. Berberine also induces mitochondrial-mediated apoptosis through the loss of mitochondrial membrane potential, cytochrome c release, caspase and PARP activation, up-regulation of pro-apoptotic Bcl-2 family proteins, and down-regulation of antiapoptotic Bcl-2 family proteins [150,[157][158][159]. It can also activate apoptosis-inducing factor to induce ROSmediated cell death in pancreatic, breast, and colon cancers [158,160,161].…”
Section: Berberinementioning
confidence: 99%
“…Berberine induces reactive oxygen species (ROS) production and activates mitochondria‐dependent apoptosis in prostate cancer cells (Meeran, Katiyar, & Katiyar, ). It also induced ROS‐mediated cell death and apoptosis in pancreatic, breast, and colon cancer through activation of apoptosis‐inducing factor (Park, Sung, Kim, & Chung, ; Wang et al, ; Xie et al, ).…”
Section: Antcancer Activitymentioning
confidence: 99%